Consequences of HIV infection in the bone marrow niche - Herd, Candice Lee; Mellet, Juanita; Mashingaidze, Tsungai; Durandt, Chrisna; Pepper, Michael Sean (Frontiers in Immunology, 2023)
Dysregulation of the bone marrow niche resulting from the direct and indirect effects of HIV infection contribute to haematological abnormalities observed in HIV patients. The bone marrow niche is a complex, multicellular environment which functions primarily in the maintenance of haematopoietic stem/progenitor cells (HSPCs). These adult stem cells are responsible for replacing blood and immune cells over the course of a lifetime. Cells of the bone marrow niche support HSPCs and help to orchestrate the quiescence, self-renewal and differentiation of HSPCs through chemical signals and cell-cell interactions. This narrative review discusses the HIVassociated dysregulation of the bone marrow niche, as well as the susceptibility of HSPCs to infection by HIV.